Analisis Prediksi Kebangkrutan dengan Menggunakan Metode Altman Z-Score pada PT. Indofood Sukses Makmur, Tbk - Try Wahyu Utami; Ali Hardana (Yayasan Literasi Sains Indonesia, 2022)
This study aims to determine the level of corporate bankruptcy using the Altman Z-Score model of the company PT. Indofood Sukses Makmur Tbk in 2012 to 2015. This study uses secondary data in the form of quantitative data. The data used in this study came from the financial statements of PT. Indofood Sukses Makmur Tbk listed on the Indonesia Stock Exchange (BEI) in the period 2012-2015.Berdasarkan Altman Z-Score method uses five variables, namely: Working capital / total assets (X1), retained earnings / total assets (X2), Earnings before interest and taxes / total assets (X3), the market value of equity / book value of debt (X4), and Sales / total assets (X5) The results in this study indicate that the model of the Altman Z-Score can be implemented in detecting the possibility of bankruptcy of the enterprise PT. Indofood Sukses Makmur Tbk. The results of the analysis show that the company PT. Indofood Sukses Makmur Tbk in 2013-2015 showed predictions of bankruptcy. It is characterized by the results of the Z-Score below 1.8, which means enormous financial difficulties and high risk. Only in 2012 who had predicted a gray area marked with a Z-Score was 1.81 <Z-Score <2.99.